2019
DOI: 10.1111/inm.12687
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ perceptions of the implementation of the transitional discharge model for community integration of psychiatric clients

Abstract: Research has demonstrated the benefits of mental healthcare interventions that ensure a safe transition of clients throughout the discharge and community integration process. This paper reports on qualitative data from focus groups with health professionals collected as part of a larger a mixed method study designed to examine the effectiveness and sustainability of implementing the transitional discharge model. Data collection involved two sets of focus groups, which were held at six months and one-year post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In particular, healthcare professionals their experience that the quality of information exchange from hospital to community is very poor, which creates challenges in implementing effective discharge planning. There are barriers to implementing effective discharge planning, such as breakdowns in communication between health professionals (Forchuk et al, 2020). Similar findings from the study also showed that poor professional collaboration and a lack of awareness of community service providers posed barriers to care coordination between internal hospitals and the community.…”
Section: Theme 2 Internal and External Barriers In Discharge Planningsupporting
confidence: 69%
See 2 more Smart Citations
“…In particular, healthcare professionals their experience that the quality of information exchange from hospital to community is very poor, which creates challenges in implementing effective discharge planning. There are barriers to implementing effective discharge planning, such as breakdowns in communication between health professionals (Forchuk et al, 2020). Similar findings from the study also showed that poor professional collaboration and a lack of awareness of community service providers posed barriers to care coordination between internal hospitals and the community.…”
Section: Theme 2 Internal and External Barriers In Discharge Planningsupporting
confidence: 69%
“…Discharge planning begins with developing education and skills, where this information must be provided to patients and families to reduce the possibility of relapse (Stuart et al, 2023). Related research on the experiences of mental healthcare professionals in implementing the transitional discharge model for the discharge of patients with mental illness from hospitals to the community resulted in four themes, namely the role and positive experiences of healthcare professionals, the perceived benefits of implementing the model, challenges in implementing the model, and suggestions for maintaining model implementation (Forchuk et al, 2020). These results are consistent with the research theme, which is the healthcare' role in assisting patients get ready for discharge by sharing their experiences and helping patients get ready for discharge.…”
Section: Discussion Theme 1 Perceptions Of Roles and Experiences In D...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such insights are significant as discharge from inpatient MHS is associated with an increased risk of suicide (Walter et al 2019). Clearly, there is a need for well-coordinated care pathways that encourage accessibility of MHS and support families in seeking help, attaining discharge readiness and providing care in their natural setting (Forchuk et al 2020;Hom et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, there is a need for well‐coordinated care pathways that encourage accessibility of MHS and support families in seeking help, attaining discharge readiness and providing care in their natural setting (Forchuk et al . 2020; Hom et al . 2015).…”
Section: Discussionmentioning
confidence: 99%